Enhancement of Thermoelectric Performance in CuSbSe2 Nanoplate‐Based Pellets by Texture Engineering and Carrier Concentration Optimization. Issue 50 (21st October 2018) - Luo, Yubo; Du, Chengfeng; Liang, Qinghua; Zheng, Yun; Zhu, Beibei; Hu, Huanlong; Khor, Khiam Aik; Xu, Jianwei; Yan, Qingyu; Kanatzidis, Mercouri G.
Abstract: This work reports the thermoelectric properties of the CuSbSe2 ‐ x mol% PtTe2 ( x = 0, 0.5, 1.0, 1.5, and 2.0) pellets composed of highly oriented single crystalline nanoplates. CuSbSe2 ‐PtTe2 single crystalline nanoplates are prepared by a wet‐chemical process, and the pellets are prepared through a bottom‐up self‐assembly of the CuSbSe2 ‐PtTe2 nanoplates and spark plasma sintering (SPS) process. X‐ray diffraction and field emission scanning electron microscopic analyses show a highly textured nature with an orientation factor of ≈0.8 for (00l) facets along the primary surface of the pellets (in‐plane, perpendicular to the SPS pressure). By this way, bulk‐single‐crystal‐like electrical and thermal transport properties with a strong anisotropy are obtained, which results in an effective optimization on thermoelectric performance. The maximum in‐plane thermoelectric figure‐of‐merit ZT value reaches 0.50 at 673 K for CuSbSe2 ‐2.0 mol% PtTe2 pellet, which is about five times higher than the in‐plane ZT (0.10) for pure CuSbSe2 . Abstract : Enhanced thermoelectric performance of CuSbSe2 based pellets with highly oriented single crystalline nanoplates are achieved by texture engineering and carrier concentration optimization, an orientation factor of ≈0.8 for (00l) facets and a high ZT value of 0.50 at 673 K are reported for CuSbSe2 ‐2.0 mol% PtTe2 sample along the primary surface of the pellets (in‐plane direction).